Revitalizing the Function of Mosques as Centers for Islamic Education: Implementation of KKNT in Bangun Sari Village, Tanjung Morawa - Abdul Aziz Shidiq; Lailan Fathiyah; Citra Sucia Hazmi; Ummi Humairah; Nasywa Zakiyah; Ananda Fitria (As-sunnah: Jurnal Pengabdian Masyarakat, 2025)
Bangun Sari Village faces challenges in Islamic education, including youth promiscuity, low interest in religious gatherings, weak Qur'anic reading skills, and minimal parental attention to children's religious education. This study aims to revitalize the mosque's function as a center for Islamic education through KKNT, using Asset-Based Community Development (ABCD) and Service Learning approaches. Service partners include community leaders, mosque administrators, BKM Istiqomah, ustadz, TPQ teachers, and residents of Bangun Sari Village Dusun XI. Data collection methods employed interviews, field observations, and Focus Group Discussions (FGD) with triangulation analysis. The program ran for two weeks (March 3-17, 2025) and encompassed youth coaching, Qur'anic tahsin guidance, Islamic studies, hijab awareness campaigns, and strategies to increase parental attention to TPQ. Results demonstrate significant improvements: youth participation in Islamic studies (80%), Qur'anic reading skills (70%), hijab awareness (60%), and parental attention to TPQ (50%). Participatory evaluation indicates program sustainability through local asset empowerment with community commitment to continue all activities post-KKNT.